STEAM concepts for infants and toddlers - Baumgart, Nichole A.; Kroll, Linda Ruth (Redleaf Press, 2018)
Illustrated vignettes narrate stories of infant and toddler STEAM (science, technology, engineering, the arts, and mathematics) concept explorations and bring out new possibilities for caregivers and educators to uncover within their own environments.